Penerapan Restorative Justice dalam Sistem Peradilan Pidana di Indonesia - Pangestu, Sultan Dwi; Pranata, Wahyu; Tanjung, Rahmatan Bilalamin; Ardianza, Habby; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Restorative justice is a criminal case resolution approach that focuses on restoring victims’ losses through dialogue among offenders, victims, and the community. This article examines the development of restorative justice in Indonesia’s criminal justice system by reviewing relevant regulations, previous studies, and practices within the police, prosecution, and judiciary. The findings show that its application has strengthened following the issuance of Prosecutor’s Regulation No. 15/2020, Police Regulation No. 8/2021, and Supreme Court Circular No. 2/2021. Although effective in reducing the workload of the justice system and providing victim recovery, its implementation still faces challenges such as limited understanding among law enforcement, potential misuse of discretion, and the absence of a specific law. The article highlights the need for stronger regulations and inter-agency coordination to ensure optimal restorative justice practices.